Peripheral Endothelial Function and Cardiovascular Events in High‐Risk Patients. Issue 6 (25th November 2013) - Matsuzawa, Yasushi; Sugiyama, Seigo; Sumida, Hitoshi; Sugamura, Koichi; Nozaki, Toshimitsu; Ohba, Keisuke; Matsubara, Junichi; Kurokawa, Hirofumi; Fujisue, Koichiro; Konishi, Masaaki; Akiyama, Eiichi; Suzuki, Hiroyuki; et al.
Abstract : Background: Endothelial dysfunction is a key component of vascular vulnerability. Reactive hyperemia index (RHI), as assessed by the peripheral arterial tonometry, can noninvasively evaluate endothelial function. This study was designed to determine the additional prognostic value of endothelial function to the Synergy Between PCI With Taxus and Cardiac Surgery Score (SYNTAXsc) and the Framingham Risk Score (FRS) in predicting cardiovascular events in high‐risk patients. Methods and Results: We undertook a two‐center prospective study in 528 stable patients at high‐risk for cardiovascular events from the years 2006–2011. The RHI was measured before coronary angiography and coronary complexity was assessed by SYNTAXsc. After optimal therapies including coronary revascularization, there was follow‐up with patients until August 2012. Cardiovascular events consist of cardiovascular death, myocardial infarction, unstable angina, ischemic stroke, coronary revascularization, heart failure‐induced hospitalization, aortic disease, and peripheral arterial disease. During 1468 person‐years of follow‐up, 105 patients developed cardiovascular events. Multivariate Cox proportional hazards analysis identified B‐type natriuretic peptide (BNP), SYNTAXsc, and RHI as independent cardiovascular event predictors (hazard ratio [95% confidence interval]: natural logarithm of BNP per 0.1: 1.019 [1.002 to 1.037]; P =0.023, SYNTAXsc per tertile: 2.426 [1.825 to 3.225]; P <0.0001, RHI per 0.1: 0.761 [0.673 to 0.859]; P <0.0001). When RHI was added to the FRS, BNP, and SYNTAXsc, net reclassification index was significantly improved (27.5%; P <0.0001), with a significant increase in the C‐statistic (from 0.728 [0.679 to 0.778] to 0.766 [0.726 to 0.806]; P =0.031). Conclusions: Advanced endothelial dysfunction significantly correlated with near future cardiovascular events in high‐risk patients. This physiological vascular measurement improved risk discrimination when added to the FRS, BNP, and SYNTAXsc. Clinical Trial Registration: URL: clinicaltrials.gov (http://www.clinicaltrials.gov ). Unique identifier: NCT00737945.